The Role of UN Women in the Implementation of SDG 5 in Conflict Area: A Case Study of Palestine - Gultom, Yosua Saut Marulitua (The Indonesian Islamic Studies and International Relations Association (Insiera), 2024)
This article discusses UN Women's role in implementing gender equality under Sustainable Development Goal (SDG) 5 in Palestine, a region prone to ongoing conflict with Israel. Women in conflict zones are often victims of physical, sexual and psychological violence and experience limited access to health and education services. UN Women, as a UN agency that focuses on gender equality, has an important role in encouraging the implementation of SDG 5 in conflict areas such as Palestine. Using descriptive qualitative research methods, this article analyzes the history and role of UN Women, the relationship between SDG 5 and conflict areas, and indications of gender inequality in the Palestinian conflict, such as violence against women and limited access to health services. Based on this analysis, the research question formulated is